Lopend Vuurtje. (Middelburg : LAVA, 1993)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Burgerweidestraat 21, 4335 GP Middelburg
LAVA = Lesbische en Andere Vrouwen Aktiviteiten
Nederlands
Periodiek